Learning Robotics Using Python : Design, Simulate, Program, and Prototype an Autonomous Mobile Robot Using ROS, OpenCV, PCL, and Python, 2nd Edition. - Joseph, Lentin (Packt Publishing Ltd, 2018)
Learning about robotics will become an essential skill as it will be a ubiquitous part of life. Even though robotics is a complex subject, several other tools along with Python can help you design a project to create an easy-to-use interface. The main aim of the book is to teach you how to build an autonomous mobile robot from scratch.